2017
DOI: 10.5430/jms.v8n4p47
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Assurance of Sustainability Report and Audit Fees

Abstract: The 21th century has seen huge changes of corporations. While companies' business grew rapidly, attention and recognition on corporate social responsibility has gradually been attracted and put on a vital strategy position. It has been proofed to be a crucial way that enterprises share their social responsibility actively in order to enhance their competitive advantage. With more and more enterprises knowing how important social responsibility is for their development, they released a new method which is calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Given the growing interest in the relationship between companies and society, a stream of research has discussed the impact of sustainability and social and environmental performance on audit fees. Zhao (2017) found that the voluntary assurance of sustainability reporting has an impact on audit fees. Carey et al (2017) examined the relationship between CSR reporting and audit fees.…”
Section: Sustainable Product Portfolios and Audit Feesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the growing interest in the relationship between companies and society, a stream of research has discussed the impact of sustainability and social and environmental performance on audit fees. Zhao (2017) found that the voluntary assurance of sustainability reporting has an impact on audit fees. Carey et al (2017) examined the relationship between CSR reporting and audit fees.…”
Section: Sustainable Product Portfolios and Audit Feesmentioning
confidence: 99%
“…Third, the sample used in the present study covers a more recent time period (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) than other studies. For example, Zhao (2017), Rabarison et al (2020) and Kim and Jung (2020) examined data from 2000-2008, 2000-2012 and 2011-2016, respectively. The time period of the present study is especially relevant because Western European countries firms have adopted sustainable practices in recent years that should be further researched.…”
Section: Introductionmentioning
confidence: 99%